Association of Ultrasound Features in Uveal Melanoma With Metastatic Risk as Defined by Preferentially Expressed Antigen in Melanoma Status - Rusakevich, Alexander M (Ophthalmic surgery, lasers & imaging retina, 2022)
BACKGROUND AND OBJECTIVE: The purpose of this study was to evaluate the association between clinical and ultrasound features of uveal melanoma and preferentially expressed antigen in melanoma (PRAME), given its role as a biomarker for metastatic mortality